Aerodynamic performance of double-wedge airfoils in supersonic flow at Mach 2 - Dhungana, Bibek; Devkota, Lochan Kendra; Adhikari, Pratik (Journal of Innovations in Engineering Education, 2026)
A systematic computational investigation is presented to evaluate the aerodynamic performance of symmetric double‑wedge airfoils operating in supersonic flow at Mach 2. Using Reynolds‑Averaged Navier–Stokes (RANS) simulations with the standard . turbulence model, the effects of thickness‑to‑chord ratio (t/c = 0.1-0.5) and angle of attack (−5° ≤ α ≤ 15°) on lift, drag, aerodynamic efficiency, and surface pressure distribution are examined. The numerical framework is validated against published experimental data at comparable Mach numbers, showing good agreement over a wide range of angles of attack. Results indicate that lift increases quasi‑linearly with angle of attack for all configurations, while drag exhibits a strong sensitivity to both angle of attack and airfoil thickness. Thinner airfoils consistently demonstrate superior lift‑to‑drag ratios, particularly at moderate angles of attack (α ≤ 5°), whereas thicker sections incur significant drag penalties due to stronger shock‑induced pressure gradients. Pressure coefficient distributions reveal a characteristic compression-expansion behavior along the chord, with stagnation pressure at the leading edge increasing markedly with thickness. The findings provide design‑relevant insights into the aerodynamic trade‑offs associated with thickness variation in double‑wedge airfoils for supersonic cruise applications.